Santi Romano and the Essay Concerning “The Nature of the Parliamentary Rules of Procedures”: Some Reading Keys (Antologia di Diritto Pubblico, 2023)
The work analyzes the essay of Santi Romano published in Modena in 1906 concerning “The nature of the Parliamentary Rules of Procedures”. The essay of Romano – a landmark in the Italian Parliamentary studies – is divided in two parts. In the first part, Romano has denied the legal nature of the Parliamentary Rules of Procedures (paragraphs 1-33). In the second part, he pointed out the impact of the Parliamentary Rules of Procedures on the interpretation and informal evolution of Constitutional law (paragraphs 34-38). The work aims to highlight the close connections between these two theses.
Keywords: parliamentary rules of procedures; Parliament; source of law; constitutional interpretation; Santi Romano